Penggunaan Sistem Mahadesa, Dropbox dan Pengerjaan Stock Opname pada PT Gerbang NTB Emas - Susanti, Lina; Dwiki Widya Karmadi, I Nengah; Ayu Sri Darmayanti, Ni Putu; Yudiaz Attabrani, Egyarda; Alpiansah, Restu (Insan Kreasi Media, 2025)
The internship aimed to provide students with hands-on experience in managing data and inventory systems through the application of Mahadesa and Dropbox at PT Gerbang NTB Emas. The implementation method involved direct observation, transaction data entry, price and stock updates, and conducting stock opname at Sweet-A Mart. During the internship, the student participated in matching physical inventory with system records, identifying discrepancies, and updating data to ensure stock accuracy. The results showed that the Mahadesa system accelerated administrative tasks and improved inventory management efficiency. The implication of this activity is that integrating information systems like Mahadesa and Dropbox significantly supports transparency and accuracy in corporate data management. PT Gerbang NTB Emas (GNE), as one of the BUMDs in West Nusa Tenggara Province, plays a strategic role in encouraging regional economic development and increasing Regional Original Income (PAD). Through the Social Community Service program required by Bumigora University, the author had the opportunity to apply management knowledge directly at PT GNE, especially in the general trade division. This experience provides a practical understanding of the world of work and application theory in business operations, as well as being an important provision in the professional development of students in the future.